Immunogenic properties of Pseudomonas aeruginosa mucoid exopolysaccharide. - Garner, C V (1990)
Previous studies have shown that antibodies to Pseudomonas aeruginosa mucoid exopolysaccharide (MEP) can be divided into two types on the basis of their functional activity. One type is able to mediate opsonic killing in conjunction with leukocytes and complement, and the other type is not. We investigated, in mice, the properties of this antigen associated with elicitation of opsonic killing antibody. We found that smaller-sized material (Kav = 0.26), which has been tested as a human vaccine, elicited opsonic killing antibody in mice at low doses (1 to 10 micrograms) and at doses of greater than or equal to 40 micrograms, only nonopsonic killing antibody was produced. A similar dose effect was seen with heat-killed mucoid P. aeruginosa cells. After immunization with high doses of this MEP or the heat-killed cells, the mice were refractory to induction of opsonic killing antibody no matter what dose of MEP was used as a booster. In contrast, a larger-molecular-weight preparation (Kav = 0.05) elicited opsonic killing antibody over a wide dose range (1 to 400 micrograms). Additionally, 50 micrograms of the larger-sized preparation could overcome the suppression induced by 50 micrograms of the smaller material. Suppression elicited by 50 micrograms of the smaller material could be adoptively transferred to nonimmune mice with the T-cell fraction of spleen cells. These results indicate that both molecular size and dose are critical determinants for eliciting opsonic killing antibody to mucoid P. aeruginosa after immunizing with MEP.